Frequently Asked Questions in Patients With Adrenal Insufficiency in the Time of COVID-19 - Sabbadin, Chiara; Betterle, Corrado; Scaroni, Carla; Ceccato, Filippo (Frontiers in Endocrinology, 2021)
Adrenal insufficiency (AI) is a life-threatening disorder, with increased morbidity and mortality, especially in case of an acute illness that can increase the requirement of cortisol. A novel infectious disease, termed Coronavirus Disease 2019 (COVID-19), appeared in 2020. Therefore, AI patients are experiencing a novel challenge: the risk of infection. In our experience, a prompt contact to the Endocrine center (with a telemedicine consultation) and a full awareness of diseases (cortisol deficiency, COVID-19 and the self-management of an adrenal crisis) are important to motivate patients. Vaccine is an effective treatment to prevent hospitalization and aggressive course of COVID-19. Some patients manifest challenges due to inequitable access and vaccine hesitancy, resulting in a delay in the acceptance of vaccines despite the availability of vaccination services. Therefore, an effort of all physicians must be conducted in order to advise patients with AI. In this short review, we try to answer some frequently asked questions regarding the management of patients with AI.